THE EFFECT OF USING BRAINSTORMING METHOD ON STUDENTS SPEAKING ACHIEVEMENT OF THE ELEVENTH YEAR STUDENTS OF SMK NEGERI 1 STABAT: ABSTRACT - Ummi Umara; Muhammad Eka Zuwanda (Jurnal Scientia, 2022)
This study was conducted as an attempt to discover the effect of using brainstorming method on students’ speaking achievement. It was an experimental research. The subject was students of Grade XI, Vocational High School (Sekolah Kejuruan Atas: SMK Negeri 1 Stabat), which consisted of 72 students as a sample of this research. The research was divided into two groups: experimental and control groups. The instrument used to collect the data was oral test. The data were analyzed by using t-test formula. The analyze showed that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group at the level of significance 0.05 with the degree of freedom (df) 70, t-observed value 4.7 > t-table value 1.99. The findings indicated that using Brainstorming Method significantly affected the students’ speaking achievement. So, English teachers are suggested to use Brainstorming method in order to improve students’ speaking achievement